Possible mechanisms underlying wheel-running-induced hypotensive effects - Susumu Sakata; Akira Nakatani; Hidefumi Waki (Japanese Society of Physical Fitness and Sports Medicine, 2014)
Physical activity of moderate intensity, like walking and jogging, can reduce the risk of developing metabolic syndrome and improve hypertension. However, such anti-hypertensive effects have yet to be fully studied. To explore the mechanisms underlying exercise-induced hypotensive effects, normotensive or hypertensive rats were subjected to voluntary wheel-running exercise. In consequence, daily wheel-running exercise appears to decrease resting blood pressure by multiple mechanisms. This short review focuses on possible mechanisms underlying the hypotensive effects of wheel-running exercise, i.e., hormonal control, nitric oxide control, sympathetic nervous control and central control in resting blood pressure regulation. To conclude, a voluntary wheel-running exercise-induced reduction in resting blood pressure may be accomplished via multiple mechanisms, i.e., a combination of 1) attenuated vasoconstriction by hormones, 2) hormone-induced reduction in blood volume, 3) hormone- and/or NO-induced vasodilation, and 4) diminished sympathetic nervous activity by body weight loss / less body weight gain, lower leptin levels and/or downregulation of serotonine 1A receptor gene in the nucleus tractus solitarii.